Territory, sovereignty and entitlement: Diplomatic discourses in the United Nations Security Council. (August 2020) - Fall, Juliet J.
Abstract: This paper builds upon feminist approaches within political science, international relations and geography that study how bodies haunt global politics, by exploring how entitlement to power connects through the scale of the body to that of the state. In a context of rising populism and political bluster, as well as post -#metoo discussions of personal entitlement displayed by well-known political figures, there is a need to take seriously how discourses of statehood within security crises are gendered in specific ways. This paper argues that the concept of entitlement offers potential for geographic enquiry by opening up new perspectives on masculinist framings of territory and state in critical geopolitics and in critical international relations. It considers specifically how diplomatic discourses ground and naturalize claims to territory by showing how states' entitlement to territory and masculinist forms of personal entitlement are connected. Drawing upon feminist approaches to language, discourse and power, this paper studies diplomatic interventions at the United Nations Security Council in New York in 2014–2017 on the crisis in Ukraine. Methodologically, it analyses diplomatic speeches through the concept of entitlement to show how territorial claims are naturalized through rhetorical devices grounded in hegemonic forms of masculinity. It argues that a clearer understanding of the connections between discourses of personal entitlement and state territorial sovereignty can further our understanding of territory.